Deciphering the bone marrow microenvironment’s role in multiple myeloma immunotherapy resistance - Nicolas Thomas Iannozzi; Nicola Giuliani; Nicola Giuliani; Paola Storti (Frontiers in Immunology)
Multiple Myeloma (MM) is a malignant monoclonal gammopathy characterized by the proliferation of plasma cells (PC) in the bone marrow (BM). The tight cross-talk between the BM microenvironment and PC is the hallmark of MM. The BM microenvironment comprises a cellular compartment, consisting of hematopoietic and non-hematopoietic cells. The first includes myeloid cells, T- and B-lymphocytes, natural killer (NK) cells, macrophages, and osteoclasts (OCs). In contrast, non-hematopoietic cell types include BM-derived mesenchymal stromal cells (MSCs), osteoblasts, adipocytes and endothelial cells. Besides the cellular compartment, there is a non-cellular compartment that includes extracellular matrix, growth factors, chemokines, and several cytokines. All these members play distinctive but interacting roles in the progression of MM and the drug response. MM remains an incurable disease, but in the last years immunotherapy has emerged as an important tool in the treatment of MM. The involvement of the BM microenvironment is a relevant barrier in the response to immunotherapy and in generating resistance. In this review, we provide an overview of the BM microenvironment perturbation in MM patients and how it can determine the possible resistance to immunotherapy, including monoclonal antibodies (mAbs), antibody-drug conjugates, chimeric antigen receptor T-cell (CAR-T), and bispecific T-cell engagers (BsAbs).